Acute effect of multiple ozone metrics on mortality by season in 34 Chinese counties in 2013–2015. (18th January 2018) - Sun, Q.; Wang, W.; Chen, C.; Ban, J.; Xu, D.; Zhu, P.; He, M. Z.; Li, T.
Abstract: Background: Although numerous multicentre studies have estimated the association between ozone exposure and mortality, there are currently no nationally representative multicentre studies of the ozone–mortality relationship in China. Objective: To investigate the effect on total (nonaccidental) and cause‐specific mortality of short‐term exposure to ambient ozone, and examine different exposure metrics. Methods: The effects of short‐term exposure to ozone were analysed using various metrics (daily 1‐h maximum, daily 8‐h maximum and daily average) on total (nonaccidental) and cause‐specific (circulatory and respiratory) mortality from 2013 to 2015 in 34 counties in 10 cities across China. We used distributed lag nonlinear models for estimating county‐specific relative risk of mortality and combined the county‐specific relative rates by conducting a random‐effects meta‐analysis. Results: In all‐year analyses, a 10 μg m −3 increase in daily average, daily 1‐h maximum and daily 8‐h maximum ozone at lag02 corresponded to an increase of 0.6% (95% CI: 0.33, 0.88), 0.26% (95% CI: 0.12, 0.39) and 0.37% (95% CI: 0.2, 0.55) in total (nonaccidental) mortality, 0.66% (95% CI: 0.28, 1.04), 0.31% (95% CI: 0.11, 0.51) and 0.39% (95% CI: 0.16, 0.62) in circulatory mortality, and 0.57% (95% CI: −0.09, 1.23), 0.11% (95% CI: −0.22, 0.44) and 0.22% (95% CI: −0.28, 0.72) in respiratory mortality, respectively. These estimates had a different seasonal pattern by cause of death. In general, the seasonal patterns were consistent with the times of year when ozone concentrations are highest. Conclusions: Our findings suggest that in China, the acute effects of ozone are more closely related to daily average exposure than any other metric.